Railway Decision Support : A Graphical user Interface to Display Train Maintenance - Flack, Oscar (2014)
The project illustrated in this report is led by eMaintenence LAB which is a part of the division of Operations and Maintenance at Luleå Technical University. The object of the thesis project was to develop a graphical user interface from a previously made thesis called Graphical Interface for eMaintenance Solutions made by Malin Bergqvist in the spring of 2013. The development should go from a paper prototype to a stage where it could be tested. To do that the paper prototype had to be programed using Microsoft visual studio.The aim of the thesis was to help eMaintenance get their graphical profile into a user interface so that they can use it in further development of their systems. The goal of the thesis was to be able to hand over a graphical user interface displayed as a Windows 8 application to use in further development of their systems.To reach the aim and goal of the thesis a literary study had to be conducted in order to gather enough information to complete the thesis and make the final concept. The literary study focuses on graphical design and user interfaces, all of this is described in the theoretical frameworks chapter.During the development some parts of the project circle process where used which is explained in the methods chapter. It basically says that the development process should go in circles where you do the steps you need to develop something over again in a circular pattern.The idea development phases where carried out by using different methods described in the methods chapter. The different methods used where individual brainstorming, experienced prototyping and mind-mapping.The system was pilot tested with eight students. All the participants were asked to do a task on each of the systems and then had to answer a couple of questionnaires. The questionnaires used were a revised version of the Computer System Usability Questionnaire and Microsoft´s Product Reaction Cards.At the end of the thesis the final concept displayed as a Windows 8 application along with this report were handed ...